Hubungan antara Efikasi Diri dengan Indeks Prestasi Kumulatif Mahasiswa Tahun Pertama di Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Ketut Witri Nurcahyani; Rima Kusuma Ningrum; Dewa Ayu Agung Alit Suka Astini (Aesculapius Medical Journal, 2024)
Self-efficacy is important for first year students because it can influence academic achievement as assessed through the grade point average. This study aims to analyze the relationship between self-efficacy and grade point average of first year students at the Faculty of Medicine and Health Sciences Warmadewa University. This research uses an analytical observational method with a cross-sectional approach with a population including all first year students in the 2022/2023 academic year. Data collection was carried out using the General Self Efficacy Scale questionnaire and secondary data on grade point average of first year students for two semesters. Next, the data will be analyzed univariately and bivariately using the IBM SPSS® version 26 application and tested with Spearman. The results showed that respondents had high self-efficacy (65.5%) and respondents had a GPA in the very satisfactory range (51.5%). The majority showed that respondents had high self efficacy and very satisfactory GPA range but the strength of the relationship between that is weak and showed in coefficient correlation is 0.212.